Pengaruh Latihan Lari Gawang Terhadap Teknik O-Soto-Gari Pada Atlet UKM Judo Di Universitas Bhayangkara Jakarta Raya Kampus II Bekasi - Maulana, Eldin; Pasaribu, Ahmad Muchlisin Natas; Candra, Juli; 'Ala, Faridatul (JURNAL ILMIAH NUSANTARA, 2025)
Some athletes from the Bhayangkara University Jakarta Raya Campus II Bekasi Judo Club are still experiencing difficulties in optimizing the O-Soto-Gari technique. This issue is believed to be related to a lack of specific and targeted physical training, particularly focusing on strengthening and agility of the leg muscles. The objective of this study is to examine the effect of hurdle running training on the O-Soto-Gari technique among judo athletes at the University of Bhayangkara Jakarta Raya Campus II Bekasi. The method used in this study is quantitative with an experimental approach to analyze the effect of hurdle running training using the drill method on the O-Soto-Gari technique. The results of this study indicate that hurdle running training using the drill method has a significant effect on improving the O-Soto-Gari technique among athletes of the Judo Club at Universitas Bhayangkara Jakarta Raya Campus II Bekasi.